PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KEUANGAN PADA USAHA KECIL DAN MENENGAH - Riadi, Riadi (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Accounting information systems are very important for small and medium enterprises (SMEs), because through a proper accounting information system, small and medium enterprises can provide complete information on the financial position of small and medium enterprises. So far, SMEs have not organized and used accounting information optimally in financial management so that the financial performance of SMEs is known . The purpose of this study was to determine the effect of accounting information systems on financial performance in SMEs. This research is a causal associative research with quantitative techniques. The population in this study are small and medium enterprises in the Tanjung Rejo Village area as many as 41 SMEs and the sample is a total population of 41 respondents. The data were analyzed using simple regression analysis and to answer the research hypothesis using the t test at a significance level of 95% ( = 0.05). The results obtained that there is an effect of accounting information systems on financial performance in small and medium enterprises.